Using AREK as Adaptive Physical Education Learning Model for Disability Vocational Students Sports - Novari Beny, Acep Ovel; Aini, Ima Kurrotun; Dermawan, Dodik Arwin; Khory, Fifuka Dwi; Windayani, Novia Restu (Journal of Vocational and Career Education, 2023)
AREK, or Asistif Rompi Elektronik Kambang, is a safety tool for blind people to help them swim and exercise. Blind people have so many problems with swimming exercises. They can sink or be guided in the middle of training. AREK can give the entry-level blind swimmer a GPS-like system that is safe from sinking incidents and accidents. Trainers can only make close contact with swimmers during the COVID-19 pandemic with a safety system and GPS guide. Level-blind swimmers can train safely in the middle of the swimming pool. Especially for students who experience special needs. The approach used is Research and Development (RD). Products using the ADDIE process remain one of the most effective tools today. Because the ADDIE model is a process that serves as a guiding framework for complex situations, it is appropriate to develop AREK to be more accessible to learners' diverse characteristics and special needs. The results in this study using AREK are very feasible, with a feasibility test by two validators with a result of 3.25 and tested by 15 blind vocational students with a result of 3.58. The conclusion is that the development of learning models is stated to be usable in blind and decent vocational students.